The impact of COVID-19 infection on multiple sclerosis disease course across 12 countries: a propensity-score-matched cohort study - David Levitz; Yi Chao Foong; Paul Sanfilippo; Tim Spelman; Louise Rath; Angie Roldan; Anoushka Lal; Mastura Monif; Vilija Jokubaitis; Serkan Ozakbas; Raed Alroughani; Cavit Boz; et al. (Therapeutic Advances in Neurological Disorders)
Background: The relationship between coronavirus disease 2019 (COVID-19) infection and multiple sclerosis (MS) relapse and disease progression remains unclear. Previous studies are limited by small sample sizes and most lack a propensity-matched control cohort. Objective: To evaluate the effect of COVID-19 infection on MS disease course with a large propensity-matched cohort. Design: This multi-centre cohort study analysed relapse and disability outcomes post-COVID-19 infection after balancing covariates using a propensity score matching method. The study period was from the 11th of September 2019 to the 16th of February 2023. The mean follow-up period was 1.7 years. Methods: Data were retrieved from the MSBase Registry. Propensity scores were obtained based on age, sex, disease duration, baseline Expanded Disability Status Scale (EDSS), MS course, relapses pre-baseline, disease-modifying therapy (DMT) class and country. Primary outcomes were time to first relapse, annualised relapse rate (ARR) and time to confirm EDSS progression. Secondary outcomes were time to EDSS of 3, 4 or 6. Sensitivity analyses with baseline DMT classes were performed. Results: The study included 2253 cases and 6441 controls. After matching, there were 2161 cases and an equal number of matched controls. Cases had a significantly higher ARR (ARR = 0.10 [95% CI 0.09–0.11]) compared to controls (ARR = 0.07 [95% CI 0.06–0.08]). Cases had a significantly greater hazard of time to first relapse compared to controls (hazard ratio (HR) = 1.54 [95% CI 1.29–1.84]). There was no association between COVID-19 infection and 24-week EDSS progression (HR = 1.18 [95% CI 0.92–1.52]), or time to EDSS of 3, 4 or 6. For patients on interferons and glatiramer acetate (BRACE), COVID-19 infection was associated with a greater hazard of time to first relapse (HR = 1.83 [95% CI 1.25–2.68]) and greater hazard of time to EDSS of 3 (HR = 2.04 [95% CI 1.06–3.90]) compared to patients on BRACE therapy without COVID-19 infection. Conclusion: COVID-19 infection was associated with a significantly increased MS relapse rate and a shorter time to first relapse. There was no effect on confirmed EDSS progression over the short term. These results support ongoing COVID-19 risk minimisation strategies to protect patients with MS.